THE PECULIARITIES OF ACTIVITIES OF SOCIONOMIC PROFESSIONS’ REPRESENTATIVES IN INTERCULARITY CONDITIONS - Pryshlyak, Oksana (Social work and education, 2018)
The article reveals the peculiarities of the activities of representatives of socionomic professions in the conditions of increasing diversification and multiculturalism of society. The essence of professional activity of representatives of socionomic professions is revealed, the purpose of which is support, development of social life of a person, harmonization of relations in society, analysis and forecasting of development and consequences of social processes. The approaches given by different scholars to the understanding of the essence and tasks of socionomic professions (T. Branick, L. Burkova, S. Vakulenko, G. Dubchak, R. Kaverina and others) are revealed. The generalized definition of socionomic professions is proposed: sociological (communicative, social) in modern science is called the type “human-human professions”, that is, professions whose main occupation is dominated by situations of interpersonal business communication. Levels of activity of representatives of socionomic professions are outlined: level of general social interaction between social, ethnocultural and religious groups (micro level); the level of social interpersonal (interobject) interaction with people, social, ethno-cultural groups (meso-level); the level of labor, professional relations in the staff (organization of staff work, the choice of strategy and tactics for the implementation of professional projects, problem solving, exchange of work experience, etc.) (macro level). The author characterized intercultural competence as a process of mastering culture, aimed at change-development, holistic formation of the personality of a specialist, the formation of a specialist as a subject of culture; social and multicultural experience that is the basis of solving vital tasks; self-identification, and acquisition of intercultural competence and cultural identity as a result of the educational process, and its components: cultural and psychological, social and cultural, reflexive and creative (personal). It is substantiated why social specialists play a key role in the realization of the tasks of multicultural education and ensuring intercultural understanding in society. The peculiarities of the activity of social specialists are revealed: human-oriented, high communicative activity, tolerance, empathy, orientation to solving problems, altruism, readiness to model situations of interpersonal interaction, lack of stereotypes and prejudices, developmental and creative nature of activity, etc.